A porous TiC supported nanostructured complex metal oxide ceramic electrode for oxygen evolution reaction - Yang, Jianye (2023)
Developing low-cost and high-performance electrodes with a customized size is greatly demanded to satisfy the industrial requirement of electrochemical water splitting. To meet this challenge, a novel binder-free electrode consisted of perovskite Sr2Fe1.4Ni0.1Mo0.5O6-δ (SFNMO) nanofibers or spinel NiCo2O4 (NCO) nanosheets tightly bonded on a porous TiC substrate has been developed to catalyze the oxygen evolution reaction in alkaline water electrolysis. The optimal SFNMO/TiC electrode requires a stable overpotential of ∼380 mV to achieve a current density of 30 mA cm−2 within 20 h of operation. The competitive OER performance of such electrode can be attributed to its unique large finger-like straight pore structure, which favors the mass transfer of electrolyte solution as well as produced oxygen bubbles. Furthermore, the strong adhesion between metal oxide catalysts and TiC substrate is derived from the interfacial reaction (form a TiCxOy solid solution), thus lowering the contact resistance of catalyst/substrate interface and promoting the charge transfer kinetics of electrodes, which leads to an outstanding catalytic performance.